2015
DOI: 10.1177/1753193415577335
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of arthroscopic reduction association of the scapholunate joint

Abstract: This study evaluates the arthroscopic reduction association scapholunate technique and outcomes. A total of 18 patients with chronic scapholunate instability with mean follow-up of 36 months were reviewed. Postoperatively, the mean visual analogue score was 2.5 and the mean DASH score was 8. The grip strength was 27 kg on the operative side compared with 32 kg on the uninjured side. The mean wrist flexion was 46° and extension was 56°. Seven patients had complications. Six patients had scapholunate joint widen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 28 publications
4
22
0
Order By: Relevance
“…In regard to the SL ligament injuries, the outcomes of reduction and association of the scaphoid and lunate (RASL) are not consistent, but many of them were still reported to be good. 9 Therefore, we believe that for the intercarpal ligament injuries in this case of 3 weeks after injury, compression the association between the carpal bones for a period of time will still work, although the results could be variable.…”
Section: Discussionmentioning
confidence: 79%
“…In regard to the SL ligament injuries, the outcomes of reduction and association of the scaphoid and lunate (RASL) are not consistent, but many of them were still reported to be good. 9 Therefore, we believe that for the intercarpal ligament injuries in this case of 3 weeks after injury, compression the association between the carpal bones for a period of time will still work, although the results could be variable.…”
Section: Discussionmentioning
confidence: 79%
“…35 Data were collected on 805 procedures from a total of 35 papers 25,[28][29][30][31][32] (Table 3). The review included 43 patients from 4 studies involving intentional fibrous nonunion type procedures, 32,41,48,61 391 patients from 14 groups involving capsulodesis, [29][30][31]39,43,47,51,52,54,55,59,60,62,63 319 patients from 12 groups involving tenodesis techniques 25,30,34,36,37,40,[44][45][46]50,53,58 and 51 patients from 4 groups using bone-tissue-bone techniques. 35,42,57,64 Overall, 68% of patients were male, and the patients' average age was 39 years (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…This is similar to other small series in the literature. [11][12][13][14] We speculate that preservation of motion across an implant will invariably lead to osteolysis and loosening. A loose implant is a known cause of pain.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Koehler et al reported on 18 patients who underwent the arthroscopically assisted RASL at a mean follow-up of 36 months. 14 The authors noted that patients with a preoperative SL interval greater than 5 mm and arthritic changes between the scaphoid and radial styloid were at a greater risk of complications or failure. In our small series, three patients had a preoperative SL interval greater than 5 mm, two of which went on to have SL interval widening with symptomatic screw osteolysis requiring hardware removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation